Tenoch's Gender Journey: Case Study of a 13-year-old Mexican Refugee with Aboriginal Ancestry - Naming the Gaps Between Theory and Practice - Tenenbaum, Silvia (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2013)
This paper explores the issues and technique that were used with a group of non-conforming youth to prepare them for successful entrance into university. It will produce and affirmation of the inner wisdom of non-traditional students as a mirror of learning for traditional teachers, to provide an example of dialogic learning through a de-colonizing lens. Then it will present the results of six years of group support and counselling to prove that denouncing the gaps in institutionalized systemic barriers to sexual minorities, coupled with persistent clincal, advocacy, and community activism, is effective in breaking the cycles of magrinalization of fervent, creative, and resilient youth once termed "at risk". Immigrant latino youth in general and the case study of Tenoch in particular shows that a direct application of present clinical practices are not enough to provide long-term healing and decolonizing attitudes to survive the academic needs of a border-gender communities. Regularm on-going therapy focused on anti-oppressive pracitces coupled with Aboriginal healing techniques has proved to be a valid, reliable, and consistent method to increase this vulnerable population's well-being without further marginalization. A practitioner might conclude that mixed model is more affirmative of individual process of personhood while still connected to one's roots and communities of origin. The implication of practice is that a clinical needs to also engage in advocacy, support, and profound transformations in order to unmask both inner and outer colonized mind traps.